Fashion wear - van Zyl, Justus (Bloemfontein: Central University of Technology, Free State, 1997)
In this script the author's main aim is a discussion of how style and sex appeal is interpreted in fashion photography. The script also involves the history offashion photography and how it developed over the years. The author's own style is described and illustrated by means of own work.
Thesis
Keywords: Fashion photography; Photography - Study and teaching - South Africa